Efficacy of salbutamol-ipratropium bromide nebulization compared to salbutamol alone in children with mild to moderate asthma attacks - Matahari Harumdini; Bambang Supriyatno; Rini Sekartini (Indonesian Pediatric Society, 2012)
Background The efficacy of salbutamol-ipratropiumbromidenebulization in children with moderate asthma attacks remainsunclear, and studies on patients with mild attacks have beenrelatively few, especially in Indonesia. However, it is commonpractice for this drug combination to be given to patients withmildô€“moderate asthma attacks.Objective To compare the efficacy of salbutamolô€“ipratropiumbromide nebulization to salbutamol alone in children v.ith mildto moderate asthma attacks.Methods This single-blind, randomized clinical trial was heldin the Department of Child Health at Cipto MangunkusumoHospital, the Tebet Community Health Center, and the MHThamrin Salemba Hospital on children aged 5ô€“18 years withmild to moderate asthma attack. We randomized subjectsto receive either 2.5 mg salbutamol plus 0.5 mg ipratropiumbromide (experimental group) or 2.5 mg salbutamol alone(control group). Nebulization was given twice, with a 20minute interval between treatments. We assessed clinicalscores, vital signs, oxygen saturations, and peak flow rates(PFRs) at baseline, and every 20 minutes up to 120 minutespost-nebulization .Results A total of 46 patients were randomized to either theexperimental or the control group. Subjects had similar baselinemeasurements. At 20 minutes postô€“nebulization, the percentageincrease of PFR was 19% higher in the experimental group(pô€€½O.OI, 95% CI 1.8 to 47.2). The proportion of PFR reversibilitywas 27% higher in the experimental group, although this resultwas statistically insignificant (P=0.06, 95% CI 0.03 to 0.52).There were no significant differences in clinical scores, oxygensaturations, respiratory rates, or hospitalization rates between thetwo groups. Side effects also did not differ significantly.Concl usion Salbutamolô€“ipratropium bromide nebulizationimproved PFR measurements better than salbutamol alone.However, other clinical parameters were not significantly differentbetween the two groups. [paediatr lndones. 2012;52:200,8].